Site fidelity and homing behaviour of intertidal sculpins revisited. Issue 1 (24th October 2016) - Knope, M. L.; Tice, K. A.; Rypkema, D. C.
Abstract : To assess the repeatability of an ecological study, this study both partially replicates and extends a previous study on the site fidelity and homing ability of two abundant and ecologically important species of rocky intertidal sculpin fishes, Oligocottus maculosus and Oligocottus snyderi . A traditional mark and recapture approach was utilized and found that both of these species display high site fidelity to a home range of tidepools and homing ability to these pools, confirming the findings of previous work. Unlike the previous study, however, there was no effect of body size on homing ability and a modelling approach that incorporates encounter probability provided evidence for a sex effect on homing ability. In addition, this study extends the maximum homing ability of O. snyderi to 179 m and O. maculosus to 218 m, which were the maximum displacement distances for each species in this study, suggesting they may be capable of even greater homing distances. This work, however, finds that homing success was negatively related to displacement distance. These findings suggest adult sculpin populations are likely to be highly sub‐structured geographically, possibly contributing to the exceptionally high species richness of the group.